Underreporting of Alcohol Use in Trauma Patients: A Retrospective Analysis. Issue 2 (April 2021) - Hoonpongsimanont, Wirachin; Ghanem, Ghadi; Chen, Yanjun; Sahota, Preet Kaur; Carroll, Christy; Barrios, Cristobal; Lotfipour, Shahram
Background: This study assessed the inconsistencies between self-reported alcohol consumption and blood alcohol content (BAC) in trauma patients. We aimed to identify the incidence of positive BAC in trauma patients who reported a zero score on the Alcohol Use Disorders Identification Test (AUDIT). We also sought to identify characteristics of individuals who were likely to negate alcohol use, yet yielded a positive BAC, to improve our ability to provide alcohol screening and healthcare to these at-risk alcohol consumers. Methods: We conducted a retrospective study from 2010 to 2018 at a university-based, level-one trauma emergency department. We identified 2581 adult trauma patients who reported a zero score on the AUDIT from the trauma registry. We collected BAC, age, gender, race, education level, mechanism of injury, language and injury severity score (ISS) from patient charts, and used descriptive analyses and multivariate logistic regression to analyze the data. Results: One hundred and thirty-one (5.08%) trauma patients who reported AUDIT of zero had a positive BAC. We found that being male (OR 1.53), assaulted or injured from a penetrating mechanism (OR 2.29) and having an ISS greater than 25 (OR 3.76) were independent positive predictors of trauma patients who reported an AUDIT of zero and had a positive BAC. Age (OR 0.99) was an independent negative predictor of trauma patients who reported an AUDIT of zero and had a positive BAC in this cohort. Conclusions: Inaccurate self-reporting of alcohol drinking behavior does exist in trauma patients. A composite of objective alcohol screening modalities, in addition to AUDIT, is needed to screen for alcohol use in this population. Healthcare providers should remain highly suspicious of alcohol-related injuries in individuals with the identified characteristics.